Does men’s support come on time? : an analysis of minimal responses in men's talk - Leila Mohajer,; Jariah Mohd. Jan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Minimal responses are the linguistic devices that are mainly used by women. They are typically regarded as cooperative enhancers. Unlike women, men use delayed minimal responses that show a lack of support, attention, and interest. Nevertheless, this paper addresses the issue of men’s language and the use of minimal responses as a strategy to build conversations cooperatively. The data of this study comprise 180 minutes of audio-recorded transcribed conversations of four groups of men who were either classmates, close friends, or both. The frequency count of minimal responses is tabulated quantitatively, and the conversation analysis approach is applied to reflect qualitative findings. The findings indicate that the stereotypical linguistic features which are assigned to men need to be reconsidered and challenged in various settings. In this study, men are as highly capable as women in selectively showing their support and interest, particularly to the issues that matter to them whenever required. This paper also references the social distance and the topic of conversation as the significant effects of minimal responses.